2017
DOI: 10.1027/2151-2604/a000288
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Students’ Implicit Theories and Their Reading Motivation

Abstract: Abstract. Parents’ and teachers’ effort feedback is considered to be an important prerequisite for children’s implicit theories of intelligence and their academic self-concepts as well as for their learning and achievement motivation. Therefore, our study examines whether differences in N = 685 primary school students’ implicit theories, their reading self-concepts, and their reading motivation can be predicted by their perceptions of their parents’ and teachers’ effort feedback on reading processes. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…This suggests that the more frequently people offer ability-focused praise, the lower their growth mindset. That is in line with previous studies on receiving praise (e.g., Hellmich & Hoya, 2017;Pomerantz & Kempner, 2013). However, there are some limitations to Study 1.…”
Section: Main Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…This suggests that the more frequently people offer ability-focused praise, the lower their growth mindset. That is in line with previous studies on receiving praise (e.g., Hellmich & Hoya, 2017;Pomerantz & Kempner, 2013). However, there are some limitations to Study 1.…”
Section: Main Analysissupporting
confidence: 88%
“…In Study 1, we examined the relationships between praise behavior and mindset about intelligence; we focused on praise between friends. As an index of praise behavior, we measured frequency of offering ability-focused and effort-focused praise based on previous studies (Hellmich & Hoya, 2017;Pomerantz & Kempner, 2013). Frequency of praise is often used in field studies on receiving praise, and research showed that the more frequently children received ability-focused praise from parents in daily life, the less they endorsed the growth mindset (Pomerantz & Kempner, 2013).…”
Section: Studymentioning
confidence: 99%
“…Adolescents frequently adopt new behaviours and ways of thinking that lead to increased independence, selfsufficiency, and expression of familiarity with others. Finding ways to assist students succeed in the classroom without also looking into ways to improve their perceptions of themselves as learners can be challenging at times (Hellmich & Hoya, 2017). In addition, without helping them identify strategies to enhance their academic achievement, it is nearly hard to help them improve their self-concept.…”
Section: Physical Self-conceptmentioning
confidence: 99%
“…Broadly speaking, this research indicates that incremental theorists tend to respond better than entity theorists in the face of real or perceived failure (Cury et al, 2008;Snyder et al, 2014), including in response to negative feedback. For example, children's implicit theories of intelligence mediate the relationship between feedback and subsequent reading motivation, indicating that children's implicit theories of ability can help explain how reactions to feedback influence behavioural change (Hellmich & Hoya, 2017). Similarly, adolescents' implicit theories of ability differentially predict the effect of feedback on self-appraisals.…”
Section: Implicit Theories Of Ability and Feedback Formatmentioning
confidence: 99%